HUBUNGAN PENGETAHUAN REMAJA PUTRI DENGAN SIKAP DALAM PERAWATAN VULVA HYGIENE DI KELAS X JURUSAN ADMINISTRASI PERKANTORAN SMK IBNU SINA BATAM TAHUN 2020 - Fadhilatul Huryah; Sri Yanti Gea (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Vulva hygiene is an action to maintain the cleanliness of the outer female organs (vulva) that is done to maintain health and prevent infection. Based on the results of preliminary studies and on August 3, 2020 in young women class X majoring in Office Administration SMK Ibnu Sina Batam as many as 10 students, researchers found that 6 young women did not know about how to care for the female area. The attitude and knowledge of young women who are lacking about vulva hygiene, such as bad behavior when defecating) or Urinating clean it with unclean and misguided water when cleaning it, wearing tight panties and not absorbing sweat, rarely changing panties, rarely changing pads, it can be a trigger for reproductive health problems (Ratna, 2010). The purpose of this study is to find out the relationship of Young Women's Knowledge With Attitudes in Vulva Hygiene Care in Class X Department of Office Administration smk Ibn Sina Batam Year 2020. This type of research is quantitative research. The population in this study amounted to 33 students and sampling techniques in this study using the Total Sampling technique using the Cross Sectional approach. The variables in this study consisted of two, namely free variables (knowledge and attitude) with bound variables (vulva hygiene care). The study used instruments in the form of questionnaires. Manual data processing and analysis of frequency and bivariate distribution data using the Chi-square test. The results showed 93% were well-informed and 7% less knowledgeable and 85% were kind and 15% were less. From the results of the research obtained there is a relationship between knowledge and attitudes in vulva hygiene care in Class X Department of Office Administration smk Ibn Sina Batam in 2020 with a result of p value 0.017 < α 0.05. It can be concluded that there is a knowledge relationship with the attitude in vulva hygiene care in Class X department of office administration of Smk Ibnu Sina Batam in 2020.